Mechanization in Nigeria: What needs to be done to stimulate demand and support market growth? - Takeshima, Hiroyuki; Kennedy, Adam (Michigan State University, 2019)
Mechanization increases the power applied to agricultural operations and is one tool among many for improving farm productivity and increasing incomes for Nigeria’s farmers and processors. It alone cannot drive the transformation of agriculture (Pingali 2007). Farmers will mechanize to lower costs and ensure timeliness of operations, allowing a greater area of land to be cultivated. The demand for mechanization is therefore determined by the stage of agricultural transformation reflecting the use of complementary inputs (improved seeds, fertilizer), the intensity of farming, land holdings, and rural labor supply and thus wages. Countries across the developing world have mechanized at different rates corresponding to their level of agricultural transformation but also strongly influenced by government policies. Assessments of agricultural mechanization at the continental level have found that Nigeria has an agricultural sector characterized by both low productivity growth and low machinery growth relative to other African countries (2018, Malabo Montpellier Panel). This brief will examine some of the supply and demand side constraints that may be hindering the adoption of mechanization and outline strategies where government and donors can focus their efforts to better support farm productivity.